Veronica Kepwe, Agriculture Enterpreneur, Tanzania - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Veronica Kepwe from Tanzania shares her story on youth engagement in agriculture with IITA celebrating International Youth Day.